2016
DOI: 10.5812/hepatmon.35566
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B-Related Concerns and Anxieties Among People With Chronic Hepatitis B in Australia

Abstract: BackgroundThe psychological wellbeing of people with chronic hepatitis B (CHB) may be negatively affected due to the chronic and transmissible nature of the disease, and possible serious complications (e.g. cirrhosis and liver cancer). There are limited data investigating concerns and anxieties among people living with CHB.ObjectivesThis study examined feelings about having hepatitis B among people with CHB, including hepatitis B-related concerns and anxieties.Patients and MethodsUsing convenience sampling, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…A study of Chinese-Americans in San Francisco similarly found that hepatitis B was framed as a family matter, with affected participants keen to educate their family members and encourage them to seek testing to protect the health of the family [ 94 ]. There are suggestions that the intergenerational and endemic nature of hepatitis B in Asian communities has the capacity to “normalise” the virus in families and decouple it from stigma and shame in ways that differ quite markedly from hepatitis C and HIV [ 87 , 90 , 95 , 96 ]. Conversely, other US studies have found that migrant families can discourage testing due to the importance of maintaining “face” [ 97 ] or fear of disclosing status to family members [ 91 ].…”
Section: Families Living With Hepatitis Bmentioning
confidence: 99%
“…A study of Chinese-Americans in San Francisco similarly found that hepatitis B was framed as a family matter, with affected participants keen to educate their family members and encourage them to seek testing to protect the health of the family [ 94 ]. There are suggestions that the intergenerational and endemic nature of hepatitis B in Asian communities has the capacity to “normalise” the virus in families and decouple it from stigma and shame in ways that differ quite markedly from hepatitis C and HIV [ 87 , 90 , 95 , 96 ]. Conversely, other US studies have found that migrant families can discourage testing due to the importance of maintaining “face” [ 97 ] or fear of disclosing status to family members [ 91 ].…”
Section: Families Living With Hepatitis Bmentioning
confidence: 99%
“…We have identified three major roles for the CNC in the clinic; these are triage, case management, GP and patient support. The clinic aligns well with at least two of the Priority Actions identified in The Second Australian National Hepatitis B Strategy 2014-2017 (Australian Government Department of Health, 2014) and the NSW Hepatitis B Strategy 2014-2020 as well as recommendations of the Australian Hepatitis B Patient and Clinical Practice Survey (Hajarizadeh, Wallace, Ngo, & Richmond, 2014) and The Economic Cost and Health Burden of Liver Disease in Australia Report (Deloitte Access Economics, 2013). The nursing practice draws considerably from the successful Australian in rural settings (Nazareth et al, 2013) and in shared care arrangements experience of nurse models of hepatitis C care in a variety of settings, e.g.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies examining the prejudice experienced by hepatitis patients in the workplace (31) have shown that approximately 30% people attempt to engage in as little contact as possible with coworkers who have hepatitis and hold certain prejudices against them. Furthermore, research has shown that individuals and patients with hepatitis fear social prejudice and feel a great deal of apprehension about informing their friends and coworkers that they have the condition (18,19,32).…”
Section: Discussionmentioning
confidence: 99%
“…Such human resources are known as "hepatitis medical care coordinators," and the first group of these professionals has recently been trained, with 34 prefectural and city governments in Japan providing training courses (10). Multiple reports have shown that individuals with hepatitis suffer from a poor understanding of the disease, fatigue, the side effects of treatment, and anxiety concerning the progression of the disease, while their quality of life (QOL) is directly affected by the disease itself (11)(12)(13)(14)(15)(16)(17); in addition, several reports have indicated the existence of prejudice and discrimination against people with infectious diseases (18,19). Previous studies on support for patients with hepatitis C (20) have shown that the individual needs of each patient must be addressed, and that better understanding of individual needs is linked to increased appropriateness of the provided care.…”
Section: Introductionmentioning
confidence: 99%